Entrepreneurship in the digital universe: Tradition and renewal of academic research (Contextus - Revista Contemporânea de Economia e Gestão, 2025)
Background: Entrepreneurship is a vast and diverse field of research that plays a significant role in technological change and innovation. When we connect these dimensions, we have entrepreneurship in the digital universe. Its academic production is still fragmented and limited, with a large concentration on economic and information systems issues. An integrated and multidisciplinary understanding of the subject helps to advance and enlarge literature on digital entrepreneurship.Purpose: This article aims to systematize academic production on entrepreneurship in the digital universe, integrating contributions from different areas of knowledge that will lead to advances in future research.Method: The systematic review of academic production took place in a three-stage process. The first stage (mapping) was based on a search for articles in different national and international databases. In the second stage (refinement and expansion), we analyzed the selected research, considering consistency, relevance, and coherence. In the third stage (thematic analysis), we identified central themes with the potential to generate explanations, integrations, and problematizations to guide future research.Results: The authors provide a concise presentation of the primary results and findings of their research. The results address the research questions or hypotheses and should be logically organized. If statistical tests were utilized, report the results and the significance level, even if they are not statistically significant. In qualitative studies, present the resulting themes, categories, or theories.Conclusions: The article's main contribution is to situate academic production on entrepreneurship in the digital universe and provide paths for its renewal, considering the socio-practical, socio-constructionist perspectives and the organizations of the creative economy.